Sequence determination between blue ballpoint pens and toner using MikrosilTM casting of the intersection. Issue 4 (2nd October 2019) - Binette, Julie; Barton, Andrew; Ostrum, R.B.
Abstract: A technique was developed and assessed for use in the determination of line crossing sequence. This technique takes advantage of the transfer of both substrate topography and ink chemistry, at the line crossing intersection, to a Mikrosil™ casting compound. An initial pilot involving intersections between blue ballpoint inks and toner was constructed and blind tested using Forensic Document Examiners at the Canada Border Services Agency. Following this initial pilot, a more extensive trial was constructed to assess the technique's application with a larger population of blue ballpoint pens and a larger number of document examiners.